Design and self-assembling behaviour of comb-like stereoregular cyclolinear methylsiloxane copolymers with chiral lactate groups. Issue 1 (2nd January 2019) - Petrova, Irina; Gaj, Aleksej; Pochiecha, Damian; Shcherbina, Maksim; Makarova, Nataliya N.; Bubnov, Alexej
ABSTRACT: Several new comb-like stereoregular cyclolinear methylsiloxane copolymers exhibiting the self-assembling behaviour have been designed and studied. For the resulting macromolecular materials, the chiral mesogenic unit, namely (S)-(–)-4-[1-ethoxycarbonyl)ethoxycarbonyl]phenyl-4′-[11-tetramethyldisiloxyl)-undecenyloxy)-biphenyl-4′-carboxylate, has been used as a side group to assure the mesomorphic behaviour. The mesomorphic and structural properties were studied by the polarising optical microscopy, differential scanning calorimetry and small-/wide-angle X-ray diffraction techniques. The designed copolymers form the orthogonal smectic A* and the tilted smectic C* phases over relatively broad temperature range, down to room temperatures. The obtained results are discussed in order to contribute to better understanding of the molecular architecture–nano-organisation relationship for a specific type of macromolecular system based on the lactic acid derivatives used as a flexible side groups. Graphical Abstract: